Evaluasi Penerapan Good Manufacturing Practices Produk Minuman Botanikal Jahe Siap Minum di PT XYZ - Husna, Salsabila Al; Jameelah, Maryam; Komalasari, Ema (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
In improving the quality of food products as an effort to build a competitive UMKM economic structure, it’s necessary to implement Good Manufacturing Practices to produce the quality and suitable for consumption products. GMP is used as a general reference for food industries which is designed to prevent problems related to the quality and safety of food products. The aim of this research was to evaluated the implementation of GMP for Ginger Botanical Drink product which includes 18 aspects of assessment based on the Minister of Industry's regulation regarding GMP. This research was conducted in a qualitative descriptive. The 11 respondents were employees in the management and production departments with the instruments were field observation and interview on each aspect of GMP parameters. The result of this research showed that GMP implementation at PT XYZ is classified as Level 3 with some non-conformities, there were 2 points in the mayor category from the building aspect, 2 points in the mayor category from the sanitation facilities aspect, 1 point in the mayor category and 1 point in the critical category from the machine and equipment aspect, 1 point in the mayor category from the final product aspect, 1 point in the critical category from the employee aspect, and 1 point in the mayor category from the storage aspect. This proves that the implementation of GMP at PT XYZ is still not good enough, therefore, several improvement recommendations need to be given.Keywords - Evaluation, GMP, Improvement Recommendations, UMKM.